Kerja Sama Tim Perawat Dalam Meningkatkan Keselamatan Pasien Berbasis Tri Hita Karana - Ida Ayu Desy Utami Pidada; Gede Sri Darma (Universitas Pendidikan Nasional, 2018)
ABSTRACT This study examined about the cooperation of nurse team in improving patient safety based on tri hita karana. Informant determination method of this research using purposive sampling approach, by determining key informant. Selection of informants by determining inclusion and exclusion criteria ie informants aged 20-30 years, users of hospital health facilities, in hospital for more than 5 days, personal of hospital management, and not physically and mentally disabled. The method of data collection through interviews, observation, and documentation. Data analysis techniques used with data reduction, presentation and conclusion, and verification of data validity by using data triangulation. The results of this study on teamwork of nurses are, among others, lack of coordination among nurses in implementing SPO and lack of communicative attitude of nurses in explaining matters relating to patient safety to patient and family, lack of facilities and infrastructure that support the implementation of patient safety, and discipline in carrying out a joint prayer, procurement for religious facilities and infrastructure. Efforts in dealing with this issue include the procurement of procedures and forms relating to communications, making communication forms that must be signed by nurses and verified by the head of the room or team leader, list of facilities and infrastructure preparations that support the improvement of the patient's determination in a SPO and socialized on a regular basis, to evaluate the work done by supervision method to see the level of nurse discipline in running the SPO. Procedures for praying in the Hospital, complementing facilities and infrastructure for worship purposes for patients and families and providing spiritual services